Pembangunan Industri Makanan Halal dalam Perspektif Hukum Islam - Umam, M. Shaiful; Faizah, Nur (Jurnal Keislaman, 2024)
This study examines the development of the halal food industry in Indonesia from the perspective of Islamic law. As the country with the largest Muslim population in the world, Indonesia's growth in the halal food sector has significant implications for adherence to sharia principles. The study explores how Islamic law impacts various aspects of the halal food industry, including certification processes, production standards, and product labeling. The main focus is on the application of halal principles throughout all stages of production, from raw material selection to final processing. The study also evaluates the role of sharia supervisory bodies, such as the Indonesian Ulema Council (MUI), in ensuring compliance with Islamic law. The findings reveal that the application of Islamic law in the halal food industry not only ensures adherence to sharia principles but also enhances consumer trust and strengthens Indonesia’s position as a global hub for the halal food industry. This study provides insights into the challenges and opportunities in advancing the halal food industry in accordance with Islamic law in Indonesia